2013
DOI: 10.1590/s1679-45082013000200023
|View full text |Cite
|
Sign up to set email alerts
|

New World Health Organization reference values for semen analysis: where do we stand?

Abstract: Semen analysis is of paramount importance to study potential male fertility, couple's infertility, the effects of gonadotoxic agents on spermatogenesis and as follow-up test during treatment of male infertility. Since 1987, the World Health Organization proposes the standardization of this test and its reference values based on population-based data. The latest version of the World Health Organization guidelines was published in 2010. It introduced a new methodology that produced new references values, which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
(12 reference statements)
0
4
0
1
Order By: Relevance
“…In addition, the new reference values were derived from data belonging to fertile men from Europe, Australia and North America, thus ignoring the vast majority of fertile men living in Africa, Asia, Middle East and South America. Recent controlled prospective studies confirmed regional differences between countries and continents as regards semen quality (Ellekilde Bonde, ; Vieira, ). Therefore, a major concern surrounded the ability of the new reference values for human semen to represent fertile men worldwide.…”
Section: Introductionmentioning
confidence: 82%
“…In addition, the new reference values were derived from data belonging to fertile men from Europe, Australia and North America, thus ignoring the vast majority of fertile men living in Africa, Asia, Middle East and South America. Recent controlled prospective studies confirmed regional differences between countries and continents as regards semen quality (Ellekilde Bonde, ; Vieira, ). Therefore, a major concern surrounded the ability of the new reference values for human semen to represent fertile men worldwide.…”
Section: Introductionmentioning
confidence: 82%
“…As per the WHO's amended guidelines, their male partners' semen analytical parameters were normal. 13 Intervention: Group I: 100 cases received letrozole (FEMARA 2.5 MG, Novartis company) (dose: 5.0 mg/d −1 on the 3 rd -7 th days of the menstrual period for five consecutive days). If the patient did not conceive, the therapy has been repeated for another cycle.…”
Section: Methodsmentioning
confidence: 99%
“…The first stage of the fertility assessment method involves analyzing the sperm count, morphology, and motility of the semen. Additional investigations such as sperm chromatin evaluation, acrosome response, ROS, and chemical testing of SP are also feasible [ 72 ]. It is essential to perform several analyses in order to have a more complete understanding of fecundity.…”
Section: Current Status Of Male Infertility Assessment and Indexes Fo...mentioning
confidence: 99%